2023
DOI: 10.1007/s00415-023-11733-y
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis, respiratory function, and respiratory tract disease

Abstract: Myasthenia gravis (MG) is characterized by muscle weakness caused by autoantibodies that bind to the postsynaptic membrane at the neuromuscular junction and impair acetylcholine receptor function. Weakness of respiratory muscles represents the most severe MG manifestation, and 10–15% of all patients experience an MG crisis with the need of mechanical ventilatory support at least once in their life. MG patients with respiratory muscle weakness need active immunosuppressive drug treatment long term, and they nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
(149 reference statements)
0
0
0
Order By: Relevance
“…A large prospective study with 25,639 participants demonstrated that participants with poorer lung function (lower FEV 1 ) are at greater risk of total and cardiovascular mortality, even in the absence of cardiovascular disease [21]. This appears to be particularly important in elderly MG patients, who may experience a high total cardiopulmonary load [3]. In our study, a lower HRV (HF, PSD) was negatively associated with peak inspiratory flow parameters, potentially resulting in inspiratory flow limitations, increased inspiratory effort due to high intrathoracic pressure, and a higher amount of work required for breathing [3,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A large prospective study with 25,639 participants demonstrated that participants with poorer lung function (lower FEV 1 ) are at greater risk of total and cardiovascular mortality, even in the absence of cardiovascular disease [21]. This appears to be particularly important in elderly MG patients, who may experience a high total cardiopulmonary load [3]. In our study, a lower HRV (HF, PSD) was negatively associated with peak inspiratory flow parameters, potentially resulting in inspiratory flow limitations, increased inspiratory effort due to high intrathoracic pressure, and a higher amount of work required for breathing [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be particularly important in elderly MG patients, who may experience a high total cardiopulmonary load [3]. In our study, a lower HRV (HF, PSD) was negatively associated with peak inspiratory flow parameters, potentially resulting in inspiratory flow limitations, increased inspiratory effort due to high intrathoracic pressure, and a higher amount of work required for breathing [3,14]. Previous studies suggest an inverse relationship between lung hyperinflation and cardiac function, which includes the cardiac preload, BRS, and HRV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations